Stretching the Definitions? Pneumatology and 'Syncretism' in African Pentecostalism - Anderson, Allan H. (Journal of Pentecostal Theology, 2001)
Some observers regard as 'syncretistic' many forms of African Pentecostalism that have developed a pneumatology with a presumed link to the pre-Christian past, and will also deny the term 'Pentecostal' to these groups. This does not fully recognise the parallels between biblical pneumatology and the holistic African worldview, and the significant contribution that African Pentecostalism makes to a dynamic understanding of pneumatology. This encounter between African religions and biblical pneumatology reflects a genuine desire to make the doctrine of the Spirit relevant in an African context. This is supported by biblical texts, where such a 'dynamic pneumatology' is assumed.
Paid
Keywords: AFRICA; GHANA; HOLY Spirit; PENTECOSTALS; RELIGION; SYNCRETISM (Religion)